S100A8 and S100A9 Are Associated with Doxorubicin-Induced Cardiotoxicity in the Heart of Diabetic Mice - Pei, Xiao M.; Tam, Bjorn T.; Sin, Thomas K.; Wang, Feng F.; Yung, Benjamin Y.; Chan, Lawrence W.; Wong, Cesar S.; Ying, Michael; Lai, Christopher W.; Siu, Parco M. (Frontiers in Physiology, 2016)
Cardiomyopathy is a clinical problem that occurs in the hearts of type 2 diabetic patients as well as cancer patients undergoing doxorubicin chemotherapy. The number of diabetic cancer patients is increasing but surprisingly the cardiac damaging effects of doxorubicin, a commonly used chemotherapeutic drug, on diabetic hearts have not been well-examined. As the signaling mechanisms of the doxorubicin-induced cardiomyopathy in type 2 diabetic heart are largely unknown, this study examined the molecular signaling pathways that are responsible for the doxorubicin-induced cardiotoxicity in type 2 diabetic hearts. Male 14- to 18-week-old db/db mice were used as the type 2 diabetic model, and age-matched non-diabetic db/+ mice served as controls. The db/+ non-diabetic and db/db diabetic mice were randomly assigned to the following groups: db/+CON, db/+DOX-5d, db/+DOX-7d, db/dbCON, db/dbDOX-5d, and db/dbDOX-7d. Mice assigned to doxorubicin (DOX) group were exposed to an intraperitoneal (i.p.) injection of DOX at a dose of 15 mg/kg to induce cardiomyopathy. Mice in control (CON) groups were i.p. injected with the same volume of saline instead of DOX. Mice were euthanized by overdose of ketamine and xylazine 5 days or 7 days after the DOX injection. Microarray analysis was adopted to examine the changes of the whole transcriptional profile in response to doxorubicin exposure in diabetic hearts. Ventricular fractional shortening was examined as an indicator of cardiac function by transthoracic echocardiography. The presence of diabetic cardiomyopathy in db/db mice was evident by the reduction of fractional shortening. There was a further impairment of cardiac contractile function 7 days after the DOX administration in db/db diabetic mice. According to our microarray analysis, we identified a panel of regulatory genes associated with cardiac remodeling, inflammatory response, oxidative stress, and metabolism in the DOX-induced cardiac injury in diabetic heart. The microarray results of selected genes were confirmed by real time PCR. Notably, S100A8 and S100A9 were found to have a unique specific expression pattern that was coincident with the DOX-induced cardiomyopathy in diabetic hearts. Correspondingly, NF-κB expression in diabetic hearts was increased together with the elevation of S100A8/9 and activation of p38 MAPK signaling after DOX administration, which induced cardiac inflammation